Designing an Inclusive City with Chrono-Urbanism Principles - Nur, Khilda W.; Amalia, Andi A.; Umar, Fitrawan; Hafifah, Lutfiah; Alkatiri, Aisyah A.A.; Mubarak, Khaerul; Syamsuddin, Muhammad A. (International Journal of Architectural Engineering Technology, 2023)
A study was conducted in Tallasa District, the newly developing district in Makassar, Indonesia, to examine all public facilities accessible in the Chrono-Urbanism timeframe and promote social inclusion and equal participation. The study found that while the concept may not be sustainable in the long term, potential development could be achieved through adjustments in spatial planning connections and involving a wide range of age groups in neighborhood designs. The study used the principles of proximity, diversity, density, and digitalization to analyze the concept. The results showed that only the diversity criteria almost met the accessibility and inclusiveness aspects. Applying the Chrono-Urbanism theory may encounter difficulties in regions with large populations and distinctive geographical features such as Indonesia’s archipelago. Diverse demographic characteristics, various transportation needs between different areas, and differences in economic and educational strata pose specific challenges. The complexities in managing urban spaces and ensuring proximity and accessibility become more pronounced in densely populated areas and require considerations to accommodate the unique circumstances of each region like Tallasa District in Makassar.